Performance Analysis of Nanoelectromechanical Relay-Based Field-Programmable Gate Arrays - Tian Qin; Simon J. Bleiker; Sunil Rana; Frank Niklaus; Dinesh Pamunuwa (IEEE Access, 2018)
The energy consumption of field-programmable gate arrays (FPGA) is dominated by leakage currents and dynamic energy associated with programmable interconnect. An FPGA built entirely from nanoelectromechanical (NEM) relays can effectively eliminate leakage energy losses, reduce the interconnect dynamic energy, operate at temperatures >225 °C and tolerate radiation doses in excess of 100 Mrad, while hybrid FPGAs comprising both complementary metal-oxide-semiconductor (CMOS) transistors and NEM relays (NEM-CMOS) have the potential to realize improvements in performance and energy efficiency. Large-scale integration of NEM relays, however, poses a significant engineering challenge due to the presence of moving parts. We discuss the design of FPGAs utilizing NEM relays based on a heterogeneous 3-D integration scheme, and carry out a scaling study to quantify key metrics related to performance and energy efficiency in both NEM-only and NEM-CMOS FPGAs. We show how the integration scheme has a profound effect on these metrics by changing the length of global wires. The scaling regime beyond which net performance and energy benefits is seen in NEM-CMOS over a baseline 90 nm CMOS technology is defined by an effective relay beam length of 0.5 $μ \text{m}$ , on-resistance of 200 $\text{k}Ω$ , and a via pitch of 0.4 $μ \text{m}$ , all achievable with existing process technology. For ultra-low energy applications that are not performance critical, NEM-only FPGAs can provide close to $15×$ improvement in energy efficiency.